2006
DOI: 10.1016/j.jfoodeng.2005.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption and cost analysis of local parboiling processes

Abstract: This study was conducted at Gazole in the Malda district of West Bengal, India, by both the physical monitoring and questionnaire survey to evaluate the local parboiling processes (vessel, small-boiler and medium-boiler). The biomass consumption and head rice yield were measured and the market values were assessed by a questionnaire. The net present worth (NPW), payback period and internal rate of return were also determined. The parboiled rice produced under boiler processes had a higher market value (US$157.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Industrial processes are energy and capital intensive and are not suitable for small to medium scale operations at the village level (Roy et al. ). Under artisanal parboiling conditions, the soaking temperature for the variety, fire intensity, quantity of paddy, steam conservation, and distribution in the system are important to achieving high‐quality parboiled rice.…”
Section: Resultsmentioning
confidence: 99%
“…Industrial processes are energy and capital intensive and are not suitable for small to medium scale operations at the village level (Roy et al. ). Under artisanal parboiling conditions, the soaking temperature for the variety, fire intensity, quantity of paddy, steam conservation, and distribution in the system are important to achieving high‐quality parboiled rice.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal energy efficiency of rice parboiling system used in Bangladesh is very low (15-30%). The theoretical demand of thermal energy for parboiling is variously reported from 241 MJ/tonne to 460 MJ/tonne [10,13] of paddy, whereas the actual consumption of thermal energy for parboiling was found to be 1680 MJ/tonne (Table 1) and similar results was also reported as 1,659 MJ/tonne [7]. There is obviously a great potential to increase the thermal efficiency of rice parboiling system in Bangladesh.…”
Section: Energy Consumption In Different Operations Of Rice Processingmentioning
confidence: 73%
“…Rice husk is mainly used as fuel for parboiling and drying of paddy before milling. In a study conducted in West Bengal, India, it was reported that 1,659 MJ of biomass energy was consumed for rice parboiling [7]. In a study by the IDRC (International Development Research Center, Canada) it was reported that theoretically the net energy demand for hot soaking, steaming and drying were 360 MJ, 105.5 MJ and 574 MJ, respectively, to process one tonne of paddy.…”
Section: Introductionmentioning
confidence: 99%
“…Rice husk is mainly used as fuel for parboiling and drying of paddy before milling. In a study conducted in West Bengal, India, it was reported that 1,659 MJ of biomass energy was consumed for rice parboiling (Roy et al 2006). In a study by the IDRC (International Development Research Center, Canada) it was reported that theoretically the net energy demand for hot soaking, steaming and drying were 360 MJ, 105.5 MJ and 574 MJ, respectively, to process one tonne of paddy.…”
Section: Energy Conversion and Source For Various Energiesmentioning
confidence: 99%